What determines public education expenditures in a transition economy? - Inna Verbina; Abdur Chowdhury (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
Recent studies suggest that the allocation of expenditures in education matters for growth. Public education spending in many transition economies, however, is often inefficient and inequitable with education outlays misallocated across sectors. This highlights the need for an assessment of the nature of education expenditures in these countries. This paper attempts to fill the gap in the literature by estimating the determinants of education expenditures in the Russian Federation. Results from panel data analysis show that revenue and the student-population ratio have a positive impact on education expenditures while the effect of population density is negative. Three regional variables also show significant impact. The income and price elasticity of education expenditures are estimated to be 0.56 and –0.47, respectively and is comparable to studies from other countries. The results presented here raise questions about how fiscal institutions and the structure of the political process in Russia may affect the degree of resource allocation in the educational sector during the transition process. – education ; expenditure ; transition ; elasticity ; Russia
Keywords: L10; O57; 330; Bildungsökonomik; Öffentliche Bildungsausgaben; Russland